Fractal parameters of Talaromyces wortmannii as indexes of aromatic hydrocarbon pollution - Romero, Maria Cristina (2011)
Fungal morphologies by fractal geometry were studied mainly for industrial applications, but the relation with environmental factors had been scarcely described. Fungi are conspicuous degraders, so, our aims were to isolate filamentous fungi from contaminated effluents, to apply fractal geometry to fungal growth in fluid medium and to evaluate fractal parameters as pollution indexes in aromatic hydrocarbons presence. Talaromyces wortmannii was selected due to its remarkable growth with hydrocarbons, byphenil and dibenzofuran. The clump diameters with naphathalene, phenanthrene and anthracene were 1.45-1.75 mm, while with pyrere, fluranthene and benzo[a]pyrene the main morphology was larger pellets. Fractals increased with the concentrations and aromatic-rings of the pollutants, with more pronounced effects on DMF than in DSF; both values were higher for condensed pellets and lower for free filamentous forms, as the mycelium become hydrophobic. In our case, hydrophobicity depended from the hydrocarbons, yielding larger aggregates. Fractals were an effective tool to test the pollutant effects on fungal growth. In mycoremediation technologies, the mycelial growth is a significant factor that affected most of the methodologies; therefore our results could be important to decide the strategies towards the contaminated effluent remediation.